Aplicação de uma bateria de testes neuropsicológicos em idosos com Comprometimento Cognitivo Leve e Doença de Alzheimer - Mallmann, Mariana Bonotto (2016)
With the increase in the elderly population, there were also increases in the prevalence rates of cognitive problems and increased demands for accurate diagnoses for conducting treatment. Therefore, it is essential to study instruments that aid in the differential diagnosis between the processes of senescence and senility. The general objective of this research was to analyze the performance of elderly individuals with a diagnosis of mild Cognitive Impairment, probable Alzheimer's disease in the initial phase and healthy elderly, in a specific battery of neuropsychological tests. In the statistical analysis, the numerical variables of the tests of the neuropsychological battery were expressed as median, the categorical variables were expressed as absolute and relative frequency. Normality and differences in the distribution of variables were assessed by the Kolmorogov-Smirmov test and the paired comparisons using the DunnBonferroni post hoc test. Tests with a probability value <0.05 were considered significant. The results showed that all the neuropsychological tests belonging to the neuropsychological battery were able to discriminate cognitive deficits when comparing the three studied populations. The Tracks test and the Frontal Evaluation Battery did not present a significant difference (= 0.252 and p = 0.39), respectively, when the comparison between the DA and CCL groups was performed. The semantic and phonological verbal fluency test did not present a significant difference when comparing the AD group and the CCL group, as well as the memory recognition part of the RAVLT test. A statistically significant association was found between all tests and clinical diagnosis. In addition, patients with AD had a greater decline in all tests when compared to the healthy and CCL group. Thus, the study contributed to evidence of cognitive deficits in the elderly with CC and AD, establishing some neuropsychological patterns, which will help in the performance of effective evaluations and diagnoses, besides directing interdisciplinary intervention measures more appropriate for these populations.